PROTEROZOIC ZIRCON AGES FROM LOWER CRUSTAL GRANULITE XENOLITHS, KOLA PENINSULA, RUSSIA: EVIDENCE FOR CRUSTAL GROWTH AND REWORKING - Downes H.; Peltonen P.; Mänttäri I.; Sharkov E.V. (My University, 2002)
Lower crustal garnet granulite xenoliths from beneath the Kola-Karelian domain of the Fennoscandian Shield (Russia) were brought to the surface in Devonian lamprophyre diatremes. To establish the relationships between processes in the lower crust and geological events recorded in the upper crust, zircons from two of these xenoliths were dated by ion microprobe. One xenolith contains mainly primary magmatic zircon grains that yielded an average age of 2.47 Ga. The Kola-Karelia domain formed part of a large basaltic igneous province in the earliest Proterozoic (c. 2.45 Ga); thus, such xenoliths probably represent deep-seated equivalents of this magmatism. A second garnet granulite xenolith contained only internally featureless zircons. Most of these yielded concordant ages between 1.77-1.61 Ga. This age distribution indicates that at c. 1.7 Ga the protolith was migmatized during an event that may be related to emplacement of granites and pegmatites in the region. However, two zircon grains in the second xenolith gave much younger ages of 1.47 and 1.45 Ga. This spread in the ages is related to an unknown younger event around 1.4 Ga (or perhaps later) when the c. 1.7 Ga 'migmatite' zircons were reset to variable degrees. These zircon ages are evidence for the complex evolution of the lower crust, recording multiple events, some of which are not currently expressed on the surface.
Keywords: Fennoscandian Shield; xenoliths; lower crust; zircon; Proterozoic; Precambrian::Proterozoic; Докембрий::Протерозой